Adaptive Operational Modes of the Military Environmental Security System - Akhundov, Ramil; Mammadov, Elnur (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper develops a structured framework of adaptive operational modes for the military environmental security system under radiation and chemical threat conditions. The approach organizes system functioning into four modes: Routine, Elevated Readiness, Emergency, and Combat Contaminated. For each mode the framework specifies entry and exit criteria, objectives, role specific actions, resource posture, and communications rhythm. A compact set of functional parameters is defined, including threat level, reaction time budget, zone status, unit readiness, resource availability, and data integrity. Transitions are governed by finite state logic with conservative escalation rules, explicit hysteresis, and uncertainty weighting based on calibration state and signal quality. The integration concept aligns sensing, analytics, and command decision making through measurable performance targets such as alarm latency, source localization accuracy, and contour forecast error. The framework is designed for interoperability with heterogeneous sensors, UAV payloads, laboratory systems, and public health feeds, and it encodes legal exposure limits as machine readable policies. The expected outcomes are reduced time to action, predictable cross unit behavior, lower personnel exposure, and improved auditability for after action learning and doctrine refinement.